2018
DOI: 10.3389/fnins.2018.00312
|View full text |Cite
|
Sign up to set email alerts
|

Acute Noise Exposure Is Associated With Intrinsic Apoptosis in Murine Central Auditory Pathway

Abstract: Noise that is capable of inducing the hearing loss (NIHL) has a strong impact on the inner ear structures and causes early and most obvious pathophysiological changes in the auditory periphery. Several studies indicated that intrinsic apoptotic cell death mechanisms are the key factors inducing cellular degeneration immediately after noise exposure and are maintained for days or even weeks. In addition, studies demonstrated several changes in the central auditory system following noise exposure, consistent wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 114 publications
(166 reference statements)
1
14
0
Order By: Relevance
“…Next, we found that the noise caused significant apoptosis of hepatocytes which was related to mobilization of intrinsic pathway, indicating the mitochondrial associated cell loss might be one of the prominent features of noise associated damage as that was also present in periphery and central auditory pathway of mice suffering from noise trauma . The imbalance between oxidation and anti‐oxidation in our work might underlie the onset of NILD, given the oxidative stress facilitating apoptosis or lipid storage of hepatocytes .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Next, we found that the noise caused significant apoptosis of hepatocytes which was related to mobilization of intrinsic pathway, indicating the mitochondrial associated cell loss might be one of the prominent features of noise associated damage as that was also present in periphery and central auditory pathway of mice suffering from noise trauma . The imbalance between oxidation and anti‐oxidation in our work might underlie the onset of NILD, given the oxidative stress facilitating apoptosis or lipid storage of hepatocytes .…”
Section: Discussionmentioning
confidence: 52%
“…28 Next, we found that the noise caused significant apoptosis of hepatocytes which was related to mobilization of intrinsic pathway, 29,30 indicating the mitochondrial associated cell loss might be one of the prominent features of noise associated damage as that was also present in periphery and central auditory pathway of mice suffering from noise trauma. 31 The imbalance between oxidation and anti-oxidation in our work might underlie the onset of NILD, given the oxidative stress facilitating apoptosis or lipid storage of hepatocytes. 20,22,32 We did not notice any significant response of NAD(P)H oxidase to noise stimulation, which was different from previous reports in which the enzyme played a key role in noise-induced cochlea injury, 33 suggesting that the oxidative adjustment after noise exposure is organ-or tissue-specific.…”
Section: Discussionmentioning
confidence: 85%
“…We grouped auditory issues into separate categories of discomfort within the physical ear and hearing itself. Our outcome of ear symptoms which included pain, ringing, and congestion, captured noise‐induced hearing loss caused by extremely loud bursts of sound that strongly impact inner ear structures by damaging sensory tissue and possibly causing tinnitus . Although symptoms may subside, our measure of hearing problems which included decreased hearing, hearing aid use (or recommended use) and difficulty hearing, describes the progressive degeneration of sensory tissue that can occur over time …”
Section: Discussionmentioning
confidence: 99%
“…Cell loss in the IC and other central auditory structures could be mediated in part by upregulation and downregulation of pro-apoptotic and anti-apoptotic genes and proteins in studies of acute and permanent noise-induced hearing loss (Groschel et al, 2018).…”
Section: Contralateral Recovery Of Gene Expression Changes: Most Of Tmentioning
confidence: 99%